Ortaöğretim kurumlarında okutulan coğrafya dersi müfredatının incelenmesi - Altunkaş, Gülhan (My University, 2003)
In this study, the secondary geography education programme was analysed. The problems of the geography programme was fixed and featured the solution of this matters. Therefore it has been prepared a survey for 34 teachers who teach in the secondary schools around Fatih, Şişli, Kağıthane, Kadıköy Beşiktaş. And we also asked to 325 students some questions about geography teaching. The result was compered with the existing geography educational details. Especially the matters which were about the lessons' aims, hours and dispersions of the geography subjects according to class levels have been fixed. Nevertheless, this study is consisting some ideas about new geography educational programme which is offered by the geography teachers. Bu araştırmada, ortaöğretim kurumlarında okutulan coğrafya dersi müfredatı incelenmiştir. Program ile ilgili sorunlar tespit edilerek çözüm önerileri sunulmuştur. Problemleri tespit etmek amacıyla İstanbul'un Fatih, Şişli, Kağıthane, Kadıköy ve Beşiktaş ilçelerinde yer alan çeşitli liselerde 34 öğretmen ile 325 öğrenciye anket uygulanmış, elde edilen sonuçlar ile mevcut coğrafya müfredat karşılaştırılmıştır. Sorunların özellikle dersin amaçları, sınıflara göre dağılımı ve ders saatleri konularında yoğunlaştığı tespit edilmiştir. Çalışmada ayrıca coğrafya öğretmenlerinin uygulanmasını istedikleri müfredat hakkında bilgilere de yer verilmiştir.
Keywords: Eğitim